Contextualization of the Law of Marrying Adultery on Married by Accident Phenomenon in the Hadith History of Imam Abu Dawud - nasrulloh, nasrulloh; Nabila, Farhanah Az Zahrowani; Al Kaswy, Titi Rusydiyati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
This article contains the legal contextualization of marrying adulterers on the emergence of the phenomenon Married by Accident in Indonesia with the hadith in Sunan Abu Dawud number 2052. The discussion regarding the quality of the hadith in Sunan Abu Dawud number 2052 in its use as evidence (hujjah) and how is the correlation between the meaning of the hadith and the contextualization of the rules of marrying an adulterer in the phenomenon of married by accident is interesting to discuss seeing the position of hadith as a muttafaq source in addressing all of the problems in human life. The method used in this study is a fiqh-hadith approach using takhrij hadith. The results obtained show that the quality of the hadith prohibiting adulterous marriage on Sunan Abu Dawud number 2052 can be categorized as authentic hadith and can be used as evidence (hujjah) in the legal decision (istinbath) of marriying adulterers. Meanwhile, the meaning analysis of this hadith correlated with the Married by accident phenomenon can be known that the law of marrying an adulterer is permitted by consider the benefit in it.